Rationale and design of the IMPACT EU-trial: improve management of heart failure with procalcitonin biomarkers in cardiology (BIC)-18. (2nd January 2018) - Möckel, Martin; Slagman, Anna; Vollert, Jörn Ole; Ebmeyer, Stefan; Wiemer, Jan C.; Searle, Julia; Giannitsis, Evangelos; Kellum, John A.; Maisel, Alan
Abstract: Objectives: To evaluate the effectiveness of procalcitonin (PCT)-guided antibiotic treatment compared to current treatment practice to reduce 90-day all-cause mortality in emergency patients with shortness of breath (SOB) and suspected acute heart failure (AHF). Background: Concomitant AHF and lower respiratory tract (or other bacterial) infection in emergency patients with dyspnea are common and can be difficult to diagnose. Early and adequate initiation of antibiotic therapy (ABX) significantly improves patient outcome, but superfluous prescription of ABX maybe harmful. Methods: In a multicentre, prospective, randomized, controlled process trial with an open intervention, adult emergency patients with SOB and increased levels of natriuretic peptides will be randomized to either a standard care group or a PCT-guided group with respect to the initiation of antibiotic treatment. In the PCT-guided group, the initiation of antibiotic therapy is based on the results of acute PCT measurements at admission, using a cut-off of 0.2 ng/ml. A two-stage sample-size adaptive design is used; an interim analysis was done after completion of 50% of patients and the final sample size remained unchanged. Primary endpoint is 90-day all-cause mortality. Conclusions: The current study will provide evidence, whether the routine use of PCT in patients with suspected AHF improves outcome.